Layanan Bimbingan Klasikal dalam Pencegahan Adiksi Media Sosial di Kelas 10 MA Al-Hidayah Ibun - Gustianti, Risma; Okta Sari, Resti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the effectiveness of classical guidance services to prevent students from social media addiction. This research was conducted using a qualitative approach by collecting data through observation and evaluation of activities. The research subjects were taken from 10th grade students of MA Al-Hidayah Ibun with a total of 35 students, the reason for choosing this class is because based on observations, the 10th grade is in an age that has just entered the adolescent stage, so that their emotions are still unstable. Especially in the use of social media which is often too much. Services are provided interactively by using power points and educational videos to support services. This method was chosen to attract students to be more optimal in understanding the material provided later. After being given classical services with the topic of social media addiction, students felt the benefits of increasing their understanding of social media addiction, prevention techniques, and ethical considerations when using social media.